2019
DOI: 10.1038/s41467-019-10562-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulating intracellular fate of siRNA by endoplasmic reticulum membrane-decorated hybrid nanoplexes

Abstract: Most cationic vectors are difficult to avoid the fate of small interfering RNA (siRNA) degradation following the endosome-lysosome pathway during siRNA transfection. In this study, the endoplasmic reticulum (ER) membrane isolated from cancer cells was used to fabricate an integrative hybrid nanoplexes (EhCv/siRNA NPs) for improving siRNA transfection. Compared to the undecorated Cv/siEGFR NPs, the ER membrane-decorated EhCv/siRNA NPs exhibits a significantly higher gene silencing effect of siRNA in vitro and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…Recent research disclosed that the caveolae-mediated endocytosis route could allow gene/drug-loaded nanoparticles to bypass the lysosome and smoothly reach the cytoplasm, e.g., Song et al found that caveolae-mediated endocytosis was conductive to the robust siRNA delivery of mannose-modified trimethyl chitosan-cysteine/tripolyphosphate nanoparticles through the subcellular organelle of the Golgi-complex and endoplasmic reticulum [ 42 ]. Qiu et al designed endoplasmic reticulum (ER) membrane-decorated siRNA nanoparticles to effectively transport siRNA through the endosome–Golgi–ER pathway to avoid lysosomal degradation [ 43 ]. In this study, caveolae/lipid raft-mediated pathways dominated the cell uptake mechanism of CEL/siRNA nanocomplexes, which inferred that high transfection efficiency was attributed to the cholesterol-dependent caveolae/lipid raft mediated pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research disclosed that the caveolae-mediated endocytosis route could allow gene/drug-loaded nanoparticles to bypass the lysosome and smoothly reach the cytoplasm, e.g., Song et al found that caveolae-mediated endocytosis was conductive to the robust siRNA delivery of mannose-modified trimethyl chitosan-cysteine/tripolyphosphate nanoparticles through the subcellular organelle of the Golgi-complex and endoplasmic reticulum [ 42 ]. Qiu et al designed endoplasmic reticulum (ER) membrane-decorated siRNA nanoparticles to effectively transport siRNA through the endosome–Golgi–ER pathway to avoid lysosomal degradation [ 43 ]. In this study, caveolae/lipid raft-mediated pathways dominated the cell uptake mechanism of CEL/siRNA nanocomplexes, which inferred that high transfection efficiency was attributed to the cholesterol-dependent caveolae/lipid raft mediated pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the experiments show that siRNAloaded lipoplexes (Cv/siRNA NPs) and CCM decorated Cv/siRNA (ChCv/siRNA) have significant lower ER retention and higher lysosomes accumulation behavior than ER coated Cv/siRNA (EhCv/siRNA) (Figure 11A). This says that EhCv/siRNA did transport siRNA through the endosome-Golgi-ER pathway (Figure 11B), and thus avoiding the lysosomal degradation to enhance the therapeutic efficiency of siRNA (Qiu et al, 2019). As illustrated by the aforementioned systems, membranes derived from different cells possess particular properties.…”
Section: Cell Membranes For Rna Deliverymentioning
confidence: 94%
“…Other cell membranes derived from platelets (Zhuang et al, 2020), endoplasmic reticulum (ER) (Qiu et al, 2019), and proinflammatory leukocytes (Jun et al, 2020) have also been researched for RNA delivery with specific targeting capacity.…”
Section: Cell Membranes For Rna Deliverymentioning
confidence: 99%
“…122,123 Hence, further understanding the escape mechanism and how to enhance the escape efficiency is of great importance for siRNA drug development. Recently, Wang and colleagues 124 developed novel endoplasmic reticulum (ER) membrane-modified hybrid nanoplexes (EhCv/siRNA NPs). Compared with unmodified nanoplexes, they showed much higher RNAi activity in vitro and in vivo.…”
Section: Sirna Modificationmentioning
confidence: 99%